(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This in-depth article examines the progressive integration of artificial intelligence in the medical field of Uzbekistan, with an emphasis on predictive models poised for early disease detection. By framing this technological transformation in the unique context of Uzbekistan’s healthcare challenges, the piece aims to highlight the implications, promises, and systematic approaches required for effective deployment of artificial intelligence within the nation’s medical infrastructure. The discussion spans how AI might address access disparities, data quality concerns, and ethical challenges, ultimately considering future strategies for embedding predictive analytics into routine healthcare while fostering public trust and clinical utility.